2004
DOI: 10.1158/1078-0432.ccr-03-0667
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pancreatic Cancer Cells with Dicumarol Induces Cytotoxicity and Oxidative Stress

Abstract: Conclusions: Inhibition of NQO 1 with dicumarol induces cell killing and oxidative stress in pancreatic cancer cells and speculate that dicumarol may prove to be useful in pancreatic cancer therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 35 publications
6
62
1
Order By: Relevance
“…Dicoumarol has been reported to have various functions through inhibition of NQO1, including accumulation Dicoumarol-mediated enhancement of CDDP cytotxicity J Watanabe et al of intracellular reactive oxygen species (ROS) (Lewis et al, 2004) or abrogation of p53 protein (Asher et al, 2001;Anwar et al, 2003). Ubiquitous expression of NQO1 was confirmed in the examined cell lines, and these cells also presented the almost similar sensitivity to dicoumarol.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Dicoumarol has been reported to have various functions through inhibition of NQO1, including accumulation Dicoumarol-mediated enhancement of CDDP cytotxicity J Watanabe et al of intracellular reactive oxygen species (ROS) (Lewis et al, 2004) or abrogation of p53 protein (Asher et al, 2001;Anwar et al, 2003). Ubiquitous expression of NQO1 was confirmed in the examined cell lines, and these cells also presented the almost similar sensitivity to dicoumarol.…”
Section: Discussionmentioning
confidence: 68%
“…As for its role in cancer, NQO1 is thought to protect cancer cells because it acts as a detoxification enzyme that removes free radicals and makes cells resistant to anticancer agents that induce oxidative injury (Danson et al, 2004). 3-3 0 -Methylene-bis [4-hydroxycoumarin] (dicoumarol) was characterized as an enzymatic inhibitor of NQO1 and was shown to inhibit proliferation of pancreatic cancer cells through an accumulation of oxidative stress (Madari et al, 2003;Lewis et al, 2004). In addition, dicoumarol induced p53 degradation through NQO1 inhibition and modulated p53-mediated apoptosis in g-irradiated normal thymocyte (Asher et al, 2001;Anwar et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Vaquero et al [51] reported that ROS produced by Nox4 are prosurvival and antiapoptotic for human pancreatic adenocarcinoma cell lines, MIA PaCa-2 and PANC-1. In the MIA PaCa-2 cell line, Lewis et al [52] showed that inhibition of NQO1 by dicoumarol suppresses the malignant phenotype of pancreatic cancer cells and induces cell apoptosis. Finally, our study described 4 quinones derivatives especially AA-861 and tBuBHQ capable of enhancing Nox4 ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Lewis et al reported that cell viability decreases to 60% when incubated with 100M dicoumarol for 48 hours. 39 These results suggest that NQO1 contributes minimally to the reduction of vitamin K to KH 2 in the vitamin K cycle. Therefore, another, still-unidentified dicoumarol/warfarininsensitive enzyme must be the major antidotal enzyme that reduces vitamin K in HEK293 cells.…”
mentioning
confidence: 82%